Atuação multifuncional dos órgãos centrais de controle interno na sustentabilidade fiscal dos entes subnacionais - Toscano Júnior, Eudes Moacir (2024)
The research investigated the impact of implementing the ombudsman and correctional macrofunctions in the Central Internal Control Units of subnational entities on fiscal management. Using the Generalized Synthetic Control method, the study measured the causal effect of these initiatives on the debt level, expressed as the ratio between Net Consolidated Debt (NCD) and Net Current Revenue (NCR). The findings indicate a temporary reduction in state indebtedness shortly after the adoption of these macrofunctions, underscoring their initial positive influence on fiscal sustainability. The average treatment effect on the treated (ATT) for correction showed a 16.48% decrease in the debt level, revealing a nonlinear trajectory with a subsequent upward trend over time. However, this trend remains subject to reversal due to external factors and institutional adjustments. Auxiliary analyses suggest that the initial gains stem from enhanced governance and transparency promoted by the implementation of correctional measures in the Central Internal Control Units, reinforcing the importance of this strategy for fiscal sustainability.